Chemical and electrochemical synthesis of cobalt hydroxides: selective phase transformation and application to distinct electrocatalytic reactions. Issue 22 (18th May 2022) - Park, Joon Yong; Kim, Ha Young; Kim, Yong-Il; Jo, So Yeong; Abbas, Syed Asad; Seo, Dongho; Ma, Ahyeon; Nam, Ki Min
Abstract : Electrochemical and chemical phase transformations of α-Co(OH)2 into various other cobalt hydroxides were performed, and their structures were characterized to discern the correlation between electrocatalytic activity and crystal structure. Abstract : Individual cobalt hydroxides with clearly identified crystal structures can aid in discerning the relationship between the crystal structure and catalytic activity. Herein, the crystal structure of α-Co(OH)2 and its transformations to other cobalt hydroxides are fully investigated. The α-Co(OH)2 structure comprised a layered structure with anion intercalation, [Co Oh 0.77 Co Td 0.23 (OH)1.77 ] 0.23+ [Cl0.23 ·0.64H2 O], which was identified by Rietveld refinement analysis using X-ray diffraction. Phase transformations of metastable α-Co(OH)2 into various other cobalt hydroxides, such as β-Co(OH)2, γ-CoOOH, and β-CoOOH, were selectively performed through a variation in the chemical environment, and their structures were fully characterized. In addition, electrochemical oxidative transformations of α-Co(OH)2 and β-Co(OH)2 into γ-CoOOH and β-CoOOH, respectively, were successfully accomplished. The prepared cobalt hydroxides were applied to the oxygen evolution reaction (OER) and chloride oxidation reaction (COR) to investigate the correlation between the crystal structure and activity. The γ-CoOOH showed better OER catalytic activity than β-CoOOH. In contrast, β-CoOOH showed higher COR selectivity than γ-CoOOH. Interestingly, the faradaic efficiency of the COR was over 97% on β-CoOOH at a concentration of 0.1 M NaCl, and this value is the highest COR faradaic efficiency compared to all other electrodes. The importance of the crystal structure for each electrocatalytic reaction is elucidated.